Antibacterial Properties of Functionalized Gold Nanoparticles and Their Application in Oral Biology. (18th November 2020) - Su, Chen; Huang, Kun; Li, Hao-Hong; Lu, You-Guang; Zheng, Da-Li
Abstract : As bacterial resistance is becoming increasingly serious, the development of antibacterial nanomaterials is an effective method of solving this problem. Gold nanoparticles have good stability and excellent biocompatibility and are easily modified, and their antibacterial properties can be enhanced by changing their structure and size or adding ingredients. Gold nanoparticles are also excellent drug carriers that can improve the antibacterial effects of loaded antibacterial drugs. After being modified and combined with other antibacterial drugs, gold nanoparticles can also play a better antibacterial role for effective antibacterial strategies against some resistant bacteria. Gold nanoparticles have photothermal effects, and modified gold nanoparticles can be a good medium for photothermal treatments to kill bacteria. By adding functionally modified gold nanoparticles, many materials can obtain much needed antibacterial properties. Gold nanoparticles can also be combined with cations, low-temperature plasma, various surface ligands, and other potential antibacterial agents. In short, the antibacterial characteristics of functionalized gold nanoparticles demonstrate that they have considerable practical application value and provide more ideas to solve antibacterial problems. At the same time, the application of gold nanoparticles in oral biology is also increasing.